Зарим хот орчмын цацраг идэвхийг гамма спектрометрээр судалсан нь - Н, Норов; С, Даваа; Д, Шагжжамба (Scientific transaction of the National University of Mongolia. Physics, 2022)
The specific radioactivity concentrations of 225Ra, 232Th, 40K and 137Cs were measured in soil samples from some city in Mongolia, using a gamma-ray spectrometer with a HpGe-detector. The background radiation of the total natural and anthropogenic radioactivity in thr studied soil was estimated.